Risk assessment and reduction options for Cryphonectria parasitica in the EU. (22nd December 2016) - ,; Jeger, Michael; Bragard, Claude; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; Parnell, Stephen; Potting, Roel; et al.
Abstract: Following a request from the European Commission, the EFSA Plant Health (PLH) Panel performed a risk assessment for Cryphonectria parasitica in the EU with the aim to assess the current EU phytosanitary requirements and identify the risk reduction options (RROs), which would preserve the protected zone (PZ) status in some parts of the EU, where the pathogen is not known to occur. C. parasitica, a bark‐inhabiting fungus causing blight of chestnut trees ( Castanea spp.), has a wide distribution in the EU (non‐PZs). Three regulatory scenarios were considered for the whole risk assessment (RA) area: the current situation in non‐PZs (scenario A0 ), the situation in the EU without measures (A1 ) and the current situation in PZs with additional RROs (A2 ). The Panel considered both the risk of potential spread to PZs of C. parasitica strains currently present in the non‐PZs and the risk of introduction from Third Countries and spread in non‐PZs of new, virulent strains that would be able to jeopardise the currently effective hypovirulence and cause severe impact. The number of new introductions of C. parasitica into the EU is reduced by approximately a factor 5, 000 (median values) in scenario A2 compared to scenario A0 . Under the A0, A1 and A2 scenarios, 2, 3.5 and 0.5 (median values) EU Member States, respectively, are expected to be affected in the next 10 years due to spread of C. parasitica strains. The estimated relative impact on ecosystem services, due to the introduction and spread in the EU of new, virulent strains, is higher for scenario A1 compared to scenarios A0 and A2 . The current EU requirements and the additional RROs considered in scenario A2 were assessed to be effective in reducing the risk of introduction and spread of C. parasitica, thus preserving the PZ status in some parts of the EU.